2019
DOI: 10.1002/slct.201900662
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Proton‐Conducting Graphene Sheets via Block Copolymer Supramolecular Assembly and Their Application for Highly Transparent Moisture‐Sensing Conductive Coating

Abstract: Here, we have demonstrated a well-defined strategy to prepare highly sulphonated reduced graphene oxide (S-rGO) sheets via non-covalent modification of rGO with water soluble rod-coil conjugated block copolymer poly(3-hexylthiophene)-block-poly (4-styrenesulfonic acid) (P3HT-b-PSSA) carrying a long PSSA block. S-rGO sheets are highly water soluble and its aqueous solution can be used to fabricate highly transparent conductive thin film coating on versatile smooth substrate surfaces like glass, indium tin oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The protons also can diffuse freely throughout the material from a high density side to a low density side through a continuous proton-conducting channel. The microphase separation of the block copolymer anchored on the RGO surface creates oriented nanochannels (pore diameter of 5–20 nm, as supported by FESEM, Figure b) filled with sulfonic acid groups, and proton transport occurs through these channels . During desorption of water molecules, the free H + will again drift back and recombine with the unmovable −SO 3 – ion, which hence induces a reverse potential or current.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The protons also can diffuse freely throughout the material from a high density side to a low density side through a continuous proton-conducting channel. The microphase separation of the block copolymer anchored on the RGO surface creates oriented nanochannels (pore diameter of 5–20 nm, as supported by FESEM, Figure b) filled with sulfonic acid groups, and proton transport occurs through these channels . During desorption of water molecules, the free H + will again drift back and recombine with the unmovable −SO 3 – ion, which hence induces a reverse potential or current.…”
Section: Resultsmentioning
confidence: 88%
“…The microphase separation of the block copolymer anchored on the RGO surface creates oriented nanochannels (pore diameter of 5−20 nm, as supported by FESEM, Figure 4b) filled with sulfonic acid groups, and proton transport occurs through these channels. 27 During desorption of water molecules, the free H + will again drift back and recombine with the unmovable −SO 3 − ion, which hence induces a reverse potential or current. When all the free H + will have combined to the unmovable −SO 3 − ions, any potential difference would not be observed between the two electrodes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the hydrophilic BCP, [poly(3hexythiophene)-block-poly (4-styrenesulfonic acid] (P3HT-b-PSSA) was anchored on the surface of rGO. 90,91 It was found that insertion of PSSA chains to the rGO sheets helps achieve a good alignment between the adjacent rGO layers. Also, the surface of the graphene sheets is homogeneously covered by the BCP to introduce the porous nanochannels, which was a result of microphase separation from the noncovalently bonded BCP.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…as a common impurity. [4,5] In most industrial processes, maintaining dry conditions is imperative because water contaminants can deteriorate the quality of products. Moreover, trace quantity of water can greatly affect the selectivity, product yield and efficiency of many chemical reactions.…”
Section: Introductionmentioning
confidence: 99%